DETERMINAN ADOPSI E-COMMERCE DAN PENGARUHNYA TERHADAP KINERJA UMKM DI CILACAP - Nahar Sabiti, Tiara; Jayanti , Esih; Saputro Sugiharto, Irwan (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This research aims to examine and analyze the influence of technological (X1), organizational (X2), environmental (X3), and individual (X4) factors on e-commerce adoption (Y1) as well as the influence of e-commerce adoption on MSME performance (Y2) in Cilacap. The sample in this study amounted to 104 respondents taken based on the Slovin formula calculation. The data collection technique was carried out by distributing questionnaires. Data analysis techniques used include validity tests, reliability tests, Method Successive Interval (MSI), classical assumption tests including linearity tests, normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests, multiple linear and simple linear regression analysis, hypothesis tests including tests t, F test, analysis of the coefficient of determination (R2). The t-test results in this study show that technological factors partially do not affect e-commerce adoption, while organizational, environmental, and individual factors positively and significantly affect e-commerce adoption. And the adoption of e-commerce has a positive and significant effect on the performance of MSMEs. The results of the F test show that technological, organizational, environmental, and individual factors simultaneously influence e-commerce adoption.